Biocementation promoted by bacteria in concrete recovery and soil stabilization - Batista Teles, Ismar; Aparecida Florentino, Ligiane (Revista Nacional de Gerenciamento de Cidades, 2022)
The use of intelligent and adaptable materials has been gaining ground in the construction industry, due to the ecological market demand and the awareness of investing in sustainable techniques, with low energy consumption and anthropogenic emission of carbon dioxide. The development of materials and construction methods, with energy efficiency, adaptable to environmental conditions and non-polluting has become a requirement for the progress of the sector and the future of cities. Thus, the objective of this bibliographic review is to provide an overview of the application of biocementing promoted by bacteria in the recovery of structures and soil stabilization. This technique uses minerals resulting from bacterial metabolic activities, which occur at room temperature, such as microbiologically induced calcium carbonate precipitation (MICP), to produce cementitious materials with structural functionalities, durability and without harming the environment. Several applications of this process have been proposed in civil engineering, such as the bioconcrete in the remediation of fissures, in the restoration of stones cultural heritage and in the improvement of the physical-mechanical properties of the soil, changing its resistance and permeability. Understanding how this biotechnology can change current construction strategies and solutions, integrating nature-based systems into construction projects, will be discussed in this study.